Martin Mowforth and Ian Munt: Tourism and Sustainability, New tourism in the Third World - Pokhrel, Shanti (Himalayan Journal of Sociology and Anthropology, 2011)
Martin Mowforth and Ian Munt: Tourism and Sustainability, New tourism in the Third World; Published by: Routledge, Taylor & Francis Group, London and New York (Reprinted 2001), Page: xvii, 363, ISBN 0-415-13763-2 (hardback) 0-415-13764-0 (paperback). DOI: http://dx.doi.org/10.3126/hjsa.v4i0.4679 Himalayan Journal of Sociology and Anthropology Vol.IV (2010) 254-256